Vdor psihoterapevtskih strategij v šolo - Barle Lakota, Andreja (Šolsko polje, 2010)
The teacher's mission to transfer knowledge is seriously put to the test in modern school. More and more students have been coming to school only because they have to, without any kind of desire or hope to acquire new (and, even less, interesting) knowledge there. Th e contradiction in situation is such that teachers are willing to do anything in order to enhance studentsć motivation to gain knowledge. One of more popular ideas suggesting to teachershow to motivate students to learn is the idea that the student must first feel good before he is prepared to gain knowledge. The point is not forthe teacher to be insensitive to the student; on the contrary, the teacher is obliged to create conditions for co-creating learning. The problem arises when the process of empowering the student to learn is substituted by psychotherapeutic concepts. The article states some examples from foreign school systems; however, there are certain teaching approaches already presentin Slovenia, too. The article warns against the dangers of such concepts gaining ground, where the teacher is increasingly being changed into someone who nurtures the lost individual and is losing his or her fundamental mission in the process.
Keywords: emocionalna država; emotional state; izgubljeni posameznik; lost individual; psihoterapevtski koncepti; psychotherapeutic concepts; vzgoja in izobraževanje